Autism Spectrum Symptomatology among Children with Duplication 7q11.23 Syndrome - Klein-Tasman, Bonita P. (J Autism Dev Disord, 2018)
Gold-standard diagnostic assessments of autism spectrum disorder (ASD) symptomatology were conducted on 63 children (mean CA: 8.81 years) with 7q11.23 duplication syndrome, one of the copy number variants identified by Sanders et al. (2011a) as associated with ASD. ASD classification rate was 39.6% for the Autism Diagnostic Interview-Revised and 25.4% for the Autism Diagnostic Observation Schedule-2 (ADOS-2). Based on these assessments combined with clinical judgment, 19.0% of children were diagnosed with ASD. Reasons for these discrepancies are discussed, as are differences in rate of diagnosis as a function of sex, age, and ADOS-2 module administered and differences in intellectual and adaptive behavior abilities as a function of presence or absence of ASD diagnosis and ADOS-2 module administered. Implications are addressed.